Tiamulin-Resistant Mutants of the Thermophilic Bacterium Thermus thermophilus - Erin E. Killeavy; Gerwald Jogl; Steven T. Gregory (MDPI AG, 2020)
Tiamulin is a semisynthetic pleuromutilin antibiotic that binds to the 50S ribosomal subunit A site and whose (((2-diethylamino)ethyl)thio)-acetic acid tail extends into the P site to interfere with peptide bond formation. We have isolated spontaneous tiamulin-resistant mutants of the thermophilic bacterium Thermus thermophilus, containing either single amino acid substitutions in ribosomal protein uL3 or single base substitutions in the peptidyltransferase active site of 23S rRNA. These mutations are consistent with those found in other organisms and are in close proximity to the crystallographically determined tiamulin binding site. We also conducted a cross-resistance analysis of nine other single-base substitutions in or near the peptidyltransferase active site, previously selected for resistance to structurally unrelated antibiotics. While some of the base substitutions in 23S rRNA are positioned to directly affect tiamulin-ribosome contacts, others are some distance from the tiamulin binding site, indicating an indirect mechanism of resistance. Similarly, amino acid substitutions in uL3 are predicted to act indirectly by destabilizing rRNA conformation in the active site. We interpret these observations in light of the available ribosome X-ray crystal structures. These results provide a more comprehensive profile of tiamulin resistance caused by mutations in the bacterial ribosome.